Mortars on binding alkaline activation - M. Sh. Salamanova (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. The problems of the negative impact of the carbonate technology for the production of Portland cement are hotly discussed at many scientific sites and the world community is striving to create more environmentally friendly and less energy-intensive binders. The development of clinker-free technology will allow solving many problems of a global scale, and the use of recycled or substandard material will expand the raw material base and reduce the burden on the environment.Method. When designing formulations for building mortars, it is necessary to take into account the compliance with the requirements for all mortars in general, both for plastering and for masonry, finishing, repair, etc. The study of the compositions of mortars was carried out by standard methods using a verified and certified equipment. Result. The paper presents the results of many years of work on the development of building composites based on binders of alkaline activation. Grades of solutions M75 - 150 were obtained, with the mobility of the mortar mixture Pk 1-2, shelf life of 33-120 minutes, with high adhesive strength of 0.62- 0.71 MPa. Conclusion. The proposed mortar compositions will make it possible to perform plastering, masonry and repair work requiring quick setting, and with proper adherence to the proposed recipes and methods for making mortars, it will be possible to obtain high-quality and durable material.